2012
DOI: 10.1111/j.1365-2672.2012.05270.x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial effect and mode of action of terpeneless cold-pressed Valencia orange essential oil on methicillin-resistant Staphylococcus aureus

Abstract: Aims The objective of this study was to evaluate the antistaphylococcal effect and elucidate the mechanism of action of orange essential oil against antibiotic resistant Staphylococcus aureus strains. Methods and Results Inhibitory effect of commercial orange essential oil (EO) against six S. aureus strains was tested by disc diffusion and agar dilution methods. The mechanism of EO action on MRSA was analyzed by transcriptional profiling. Morphological changes of EO treated S. aureus were examined by transmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 72 publications
(65 reference statements)
3
49
0
1
Order By: Relevance
“…Proteolysisrelated protein species were more abundant in stressed samples, and proteins damaged by cellular stress were degraded by proteasomes and proteolytic enzymes [91]. One protein species was identified in this group, peptidase M20/M25/M40 family protein (spot 4409), functions in the degradation of proteins, peptides and glycopeptides [92]; this protein was less abundant in T2 and T3 than in T1. A mammalian cell study showed that protein aggregation during oxidative stress, aging and disease can lead to decreased protealysis [93].…”
Section: Proteolysis-related Protein Speciesmentioning
confidence: 98%
“…Proteolysisrelated protein species were more abundant in stressed samples, and proteins damaged by cellular stress were degraded by proteasomes and proteolytic enzymes [91]. One protein species was identified in this group, peptidase M20/M25/M40 family protein (spot 4409), functions in the degradation of proteins, peptides and glycopeptides [92]; this protein was less abundant in T2 and T3 than in T1. A mammalian cell study showed that protein aggregation during oxidative stress, aging and disease can lead to decreased protealysis [93].…”
Section: Proteolysis-related Protein Speciesmentioning
confidence: 98%
“…Other specific effects of citrus oil on MRSA include increased expression of penicillin-binding-protein-4 (PBP 4), involved in peptidoglycan synthesis, and genes in the dltABCD operon. This operon controls alanylation of teichoic acids of the cell wall which may play a role in autolysin activity of S. aureus [32]. Autolysin activity was also suggested by Carson and coworkers who noted that tea tree oil resulted in release of membrane-bound, cell wall autolytic enzymes leading to cell lysis and death [21].…”
Section: Ancient Remedies: the Sciencementioning
confidence: 84%
“…In such cases, specificity may be related to individual essential oil components. Recently, investigators attempted to determine the mechanism of action of cold-pressed Valencia orange oil against methicillin-resistant Staphylococcus aureus (MRSA) [32]. Microarray data showed a 24-fold increase in expression of cwrA following exposure to the oil.…”
Section: Ancient Remedies: the Sciencementioning
confidence: 99%
“…Valencia orange oil (CPV) is another EO that has shown antimicrobial efficacy against S. aureus in vitro. Additionally, CPV did not exhibit any toxicity to tested keratinocyte cell lines [265]. Several other medicinal EOs are shown in Table 7.…”
Section: Natural Productsmentioning
confidence: 99%